Signals from the World of Economics. The Price Constant and the Democratic Issue - COSSIGA, Giovanni Antonio (International Journal of Social and Administrative Sciences, 2018)
Economic systems are tending naturally to stability. This trend is crucial to give meaning to those signals coming from the economy. First, the basic inflation that when is close to 2% becomes constant and independent from the economic movement. This value is certifying that the economic system is stable over time. Because of its independence from the economy movement, the basic constant price close to 2% is rather a messenger of the good relationship between social development and the environment. Otherwise, in an unstable system, price dynamics are highly influenced by the economic movement. For this subordination, therefore, on the price scale are placed the values - lower or higher than the constant value close to 2% - which are expressing the system instability. Inflation or deflation are explicit messages that the unstable system transmits to institutions, companies and families to report the deviation from the stability path. To report the health state and the environment compatibility, the natural system sends explicit but also implicit messages, which are generally perceivable by the community within a territory or area. According to this approach, we should admit that the community has a correct general information on the economy state and its deviation. On the other hand, thanks to a collective intuition that is oriented by the stability tendency of economic systems and by the general information perceived about the economy state, the community seems able to select the general program for a good governance. It follows that the democratic model is playing a role when confirming the good governance with its program, in the case of economics moving in almost stable conditions.